The role of electrolyte fluidity on the power generation characteristics of thermally driven electrochemical cells - Hasan, Syed Waqar; Said, Suhana Mohd; Shuhaimi, Ahmad; Jaffery, Hasan Abbas; Sabri, Mohd Faizul Mohd (Penerbit Universiti Kebangsaan Malaysia, 2018)
Thermally driven electrochemical cells (thermocells) are able to convert thermal gradient applied across redox electrolyte into electricity. The performance of the thermocells heavily depends on the magnitude and integrity of the applied thermal gradient. Herein, we study the iodide/triiodide (I-/I3-) based 1-Ethyl-3-methyl-imidazolium Ethylsulfate ([EMIM][EtSO4]) solutions in a thermocell. In order to comprehend the role of fluidity of the electrolyte, we prepared set of solutions by diluting [EMIM][EtSO4] with 0.002, 0.004, and 0.010 mol of Acetonitrile (ACN). We realized a significant improvement in ionic conductivity (σ) and electrochemical Seebeck (Se) of diluted electrolytes as compared to base [EMIM][EtSO4] owing to the solvent organization. However, the infra-red thermography indicated faster heat flow in ACN-diluted-[EMIM] [EtSO4] as compared to the base [EMIM][EtSO4]. Therefore, the maximum power density of base [EMIM][EtSO4] (i.e. 118.5 μW.m-2) is 3 times higher than the ACN-diluted-[EMIM][EtSO4] (i.e. 36.1 μW.m-2) because of the lower thermal conductivity. Hence this paper illustrates the compromise between the fast mass/flow transfer due to fluidity (of diluted samples) and the low thermal conductivity (of the pure [EMIM][EtSO4]).